2017
DOI: 10.1007/s00705-017-3689-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and phylogenetic analysis of megalocytivirus RSIV-Ku: A natural recombination infectious spleen and kidney necrosis virus

Abstract: Megalocytiviruses are classified into three genotypes, infectious spleen and kidney necrosis virus (ISKNV), red seabream virus (RSIV), and turbo reddish body iridovirus (TRBIV), based on the major capsid protein and ATPase genes. However, only a few complete genome sequences have been obtained. This paper reports the complete genome sequence and phylogenetic analysis of an RSIV-Ku strain megalocytivirus. The genome sequence comprises 111,154 bp, has 132 putative open reading frames, and is homologous mostly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
12
0
5
Order By: Relevance
“…However, the possible recombination likely occurred among other megalocytivirus species (GSIV, OSGIV, RSIV, RBIV, SACIV, TBIV, TRBIV, TSGIV and ISKNV) rather than between ECIV and SDDV strains since the reticulation pattern of the network, an indication of recombination, can be found exclusively among the former species (Figure 3b). In fact, the evidence of interspecies recombination between isolate RSIV‐Ku and GSIV‐K1 has been reported previously, which is consistent with the network analysis result obtained in this study (Shiu, Hong, Ku, & Wen, 2018). Regarding the genetic components, a unique 7.6‐kb‐long genomic region was found in TH2019 but not in the reference genome (Figure 4), giving more understanding about genomic structure and diversity of SDDV.…”
Section: Discussionsupporting
confidence: 93%
“…However, the possible recombination likely occurred among other megalocytivirus species (GSIV, OSGIV, RSIV, RBIV, SACIV, TBIV, TRBIV, TSGIV and ISKNV) rather than between ECIV and SDDV strains since the reticulation pattern of the network, an indication of recombination, can be found exclusively among the former species (Figure 3b). In fact, the evidence of interspecies recombination between isolate RSIV‐Ku and GSIV‐K1 has been reported previously, which is consistent with the network analysis result obtained in this study (Shiu, Hong, Ku, & Wen, 2018). Regarding the genetic components, a unique 7.6‐kb‐long genomic region was found in TH2019 but not in the reference genome (Figure 4), giving more understanding about genomic structure and diversity of SDDV.…”
Section: Discussionsupporting
confidence: 93%
“…3C) showed the reticulation pattern within ISKNV and RSIV groups which implied the possible genetic recombination between the members of these groups. In fact, one of the ISKNV group members, RSIV-Ku, harbored 7% of genome contents similar to the GSIV-K1 (belonging to RSIV group) which indicated that this strain was ISKNV/RSIV recombinant [42]. Herein, possible recombination between ISKNV KU1/KU2 and other megalocytiviruses was screened using the RDP4 program [35] but no evidence of recombination was found in their genomes (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Orthology analysis showed a surprisingly high number of unassigned orthogroups (unique genes) among the genomes of ISKNN KU1/KU2, RSIV-Ku, and reference strain. It is predictable that the strain RSIV-Ku, a natural recombinant virus, may possess numerous unique genes since its genome carried a 7.8-kb-long region similar to RSIV genotype II rather than ISKNV [42]. In the case of the ISKNV reference strain, 18 genes were unassigned to any orthologous groups, though the core genome similarity comparing to the ISKNV KU1/KU2 was as high as 99.98%.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, RSIV subtype II has been identified as the major causative pathogen of endemic RSIVD in cultured marine fish in Korea [5]. Recently, an ISKNV/RSIV recombinant type was isolated from red sea bream (Pagrus major) in Taiwan, known as RSIV-Ku [13]. Its genome shares a high degree of homology with ISKNV-type viruses, except for specific nucleotide sequences that are closely related to RSIV-type viruses, implying that RSIV-Ku is a natural recombinant of ISKNV-and RSIVtype viruses [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an ISKNV/RSIV recombinant type was isolated from red sea bream (Pagrus major) in Taiwan, known as RSIV-Ku [13]. Its genome shares a high degree of homology with ISKNV-type viruses, except for specific nucleotide sequences that are closely related to RSIV-type viruses, implying that RSIV-Ku is a natural recombinant of ISKNV-and RSIVtype viruses [13]. Moreover, RSIV SB5-TY from a diseased Japanese seabass (Lateolabrax japonicus) in Korea is believed to be a genetic variant of RSIV-type viruses based on sequence difference in MCP and ankyrin repeat domains [5].…”
Section: Introductionmentioning
confidence: 99%